PENULISAN BAHAN BACAAN TEKS EKSPLANASI BERBASIS POTENSI LOKAL - Fajari, Muhammad Nurul; Daeng, Kembong; Aj, Andi Agussalim (Fakultas Teknik Universitas Negeri Makassar, 2022)
This study aims to describe the feasibility of content, language feasibility, graphic feasibility, presentation feasibility, legibility, and the effectiveness of local potential-based explanatory text reading materials in class VIII SMP Negeri in Gowa Regency. This type of research is descriptive. The data sources of this research are reading materials that have been compiled and data sources for teachers and students of class VIII SMP Negeri in Gowa Regency, which are the targets of implementing the 2013 Curriculum in the 2018/2019 academic year. Data collection techniques used are observation, interviews, questionnaires, and tests. The results of this study indicate that the content, use of language, graphics, presentation and use of local potential-based explanatory text reading materials in class VIII of SMP Negeri in Gowa Regency are declared suitable for use. In addition, the average readability of reading materials is suitable and effective reading materials are used in class VIII of SMP Negeri in Gowa Regency.